UMOTMA: Underwater multiple object tracking with memory aggregation - Hao, Zhicheng; Qiu, Jun; Zhang, Haimiao; Ren, Guangbo; Liu, Chang (Frontiers in Marine Science, 2022)
Underwater multi-object tracking (UMOT) is an important technology in marine animal ethology. It is affected by complex factors such as scattering, background interference, and occlusion, which makes it a challenging computer vision task. As a result, the stable continuation of trajectories among different targets has been the key to the tracking performance of UMOT tasks. To solve such challenges, we propose an underwater multi-object tracking algorithm based on memory aggregation (UMOTMA) to effectively associate multiple frames with targets. First, we propose a long short-term memory (LSTM)-based memory aggregation module (LSMAM) to enhance memory utilization between multiple frames. Next, LSMAM embeds LSTM into the transformer structure to save and aggregate features between multiple frames. Then, an underwater image enhancement module ME is introduced to process the original underwater images, which improves the quality and visibility of the underwater images so that the model can extract better features from the images. Finally, LSMAM and ME are integrated with a backbone network to implement the entire algorithm framework, which can fully utilize the historical information of the tracked targets. Experiments on the UMOT datasets and the underwater fish school datasets show that UMOTMA generally outperforms existing models and can maintain the stability of the target trajectory while ensuring high-quality detection. The code is available via Github.